CLINICAL SKILLS TEACHING USING PATIENT EXAMINATION VIDEO DURING THE COVID-19 PANDEMIC - Rizaldy Taslim Pinzon; Vanessa Veronica (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: The current situation of the COVID-19 pandemic has changed the clinical learning system, which was originally fully face-to-face or blended, to be fully online. Skills lab, as one of the most routine medical skills education methods in the undergraduate medical education phase, must also adapt its implementation by optimizing the full-online approach. The purpose of this review was to investigate how patient examination videos can be used as clinical skills educational tool during the COVID-19 pandemic.Learning Media Review: The selected patient video is an unedited, soundless recording of a neurologist doing a pathological reflex test at Bethesda Hospital Yogyakarta. During clinical skills laboratory sessions, videos are displayed concurrently with introductory lectures to examine abnormal reflexes.Conclusion: This study demonstrates that using actual patient videos in clinical skills sessions is acceptable and well-implemented. This is an excellent alternative method of acquiring clinical competencies during the COVID-19 pandemic era.